CORRELATION BETWEEN SOCIAL ACTIVITY LEVEL WITH DEPRESSION IN ELDERLY DURING THE COVID-19 PANDEMIC - Vincentia Prasari Setyowardhani; Yudita Wulandari; Nita Kurniawati (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Background: With the COVID-19 pandemic that’s currently happening, the Indonesian government made a policy called Pembatasan Sosial Berskala Besar (PSBB) to prevent the transmission of the COVID-19 virus. As a result of this new policy there was a change in the lives of Indonesians, like restrictions and a decrease in their social activities. The elderly are individuals who experiences a decline in various body function, which causes decreased social activities, and due to the reduction of their social activities, they’re potentially to experience depression due to feeling isolated and lonely. With this PSBB policy, the elderly whose social activities have already decreased, will potentially experience a more and massive reduction in their activities, and because of that the potential for depression will likely to increase.Objective: To determine the correlation between social activity level with depression in elderly during the COVID-19 pandemic.METHOD: The design of this research is observational analysis using a cross sectional method. The data were collected using the Australian Community Participation Questionnaire (ACPQ) and Geriatric Depression Scale (GDS). Statistical analysis test used in this research was Spearman correlation test.RESULTS: Social activities of the elderly in the moderate category were 47.2% and elderly who are not depressed were 81,5%. The results from the Spearman test were found to have a significant correlation between the two variables, p value = < 0.05. The correlation level from the test was -0.335 which indicates a low correlation level.CONCLUSION: There is a significant correlation that has a negative value, so it can be concluded that if social activity level is high, then the incidence of depression is low or non-existent. KEYWORD: Elderly, Social Activity, Depression, COVID-19 pandemic, Pembatasan Sosial Berskala Besar (PSBB).